JANA NDIAYE BERÁNKOVÁ, MICHAEL HAUSER, NICK NESBITT (edd.) – Revolutions for the Future: May ’68 and the Prague Spring: Lyon 2020, Suture Press, 321 s., ISBN 978-2-9569056-1-5 - Studený, Luboš (Dějiny – teorie – kritika, 2021)
Review.